Carborane-based BODIPY dyes: synthesis, structural analysis, photophysics and applications - Ordóñez-Hernández, Javier; Planas, José Giner; Núñez, Rosario (Frontiers in Chemistry, 2024)
Icosahedral boron clusters-based BODIPY dyes represent a cutting-edge class of compounds that merge the unique properties of boron clusters with the exceptional fluorescence characteristics of BODIPY dyes. These kinds of molecules have garnered substantial interest due to their potential applications across various fields, mainly including optoelectronics, bioimaging, and potential use as boron carriers for Boron Neutron Capture Therapy (BNCT). Carborane clusters are known for their exceptional stability, rigid geometry, and 3Daromaticity, while BODIPY dyes are renowned for their strong absorption, high fluorescence quantum yields, and photostability. The integration of carborane into BODIPY structures leverages the stability and versatility of carboranes while enhancing the photophysical properties of BODIPY-based fluorophores. This review explores the synthesis and structural diversity of boron clusters-based BODIPY dyes, highlighting how carborane incorporation can lead to significant changes in the electronic and optical properties of the dyes. We discuss the enhanced photophysical characteristics, such as red-shifted absorption and emission poperties, charge and electronic transfer effects, and improved cellular uptake, resulting from carborane substitution. The review also delves into the diverse applications of these compounds. In bioimaging, carborane-BODIPY dyes offer superior fluorescence properties and cellular internalization, making them ideal for cell tracking. In photodynamic therapy, (PDT) these dyes can act as potent photosensitizers capable of generating reactive oxygen species (ROS) for targeted cancer treatment making them excellent candidates for PDT. Additionally, their unique electronic properties make them suitable candidates for optoelectronic applications, including organic light-emitting diodes (OLEDs) and sensors. Overall, carborane-BODIPY dyes represent a versatile and promising class of materials with significant potential for innovation in scientific and technological applications. This review aims to provide a comprehensive overview of the current state of research on carborane-BODIPY dyes, highlighting their synthesis, properties, and broad application spectrum.